Pengaruh Tingkat Profitabilitas Dan Solvabilitas Terhadap Audit Delay Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Index Saham Syariah Indonesia - Ina Sapitri; Rini Idayanti (Institut Agama Islam Negeri (IAIN) Bone, 2024)
This study aims to identify and analyze: (1) the effect of profitability on audit delay in property and real estate companies listed on ISSI from 2018 to 2022, (2) the effect of solvency on audit delay in property and real estate companies listed on ISSI from 2018 to 2022, and (3) the effect of profitability and solvency on audit delay in property and real estate companies listed on ISSI from 2018 to 2022. The population of this study comprises all property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI) from 2018 to 2022. The sampling method used is purposive sampling, with a sample of 17 companies from 2018 to 2022. The type of research data is quantitative, and the data source is secondary. The data analysis techniques used include descriptive statistics, classical assumption tests, multiple linear regression analysis, the RÂ² determination coefficient, and t-tests using SPSS 23.The results of this study show that: (1) the profitability variable has a negative effect on audit delay with a significant value of 0.000, (2) the solvency variable has a positive effect on audit delay with a significant value of 0.000, and (3) the F-test results indicate that profitability and solvency simultaneously affect audit delay.